A cautionary tale about translocating mussels and implications for conservation: A case study from two river basins in central Texas. Issue 4 (18th January 2021) - Hart, Michael A.; Fisher, Mark; Randklev, Charles R.
Abstract: Translocation is used to conserve mussels, yet there remains a debate about its merit owing to poor understating of its effects on transported mussels. This study evaluated survivorship, body condition, and total glycogen and lipids for one common and widely distributed species ( Cyclonaias pustulosa ), two rare species ( Cyclonaias petrina ; Lampsilis bracteata ), and one species complex ( Fusconaia sp. – Fusconaia chunii and Fusconaia flava ) from the East Fork of the Trinity River and the Llano River of Texas. Survivorship estimates for C. pustulosa and Fusconaia sp. using the Kaplan–Meier estimator were high in the East Fork. Body condition, glycogen, and total lipids varied for C. pustulosa and Fusconaia sp., which may have indicated a short‐term impact. For the Llano, survivorship of C. petrina and L. bracteata was high for the resident treatments but significantly reduced for the translocation treatments. The decline in survivorship for C. petrina was mirrored by decreases in the body condition, which may indicate inability to acclimate to novel environments. For L. bracteata, declines in survivorship were due to predation by Procyon lotor, racoon. A large flood of 3, 766 m 3 s −1 at the end of the study eliminated both study sites. The findings of this study show that translocating mussels can be successful; however, sublethal effects and mortality may still occur. These effects are rooted in species‐specific differences, which is not unexpected because mussel species vary in how they cope with environmental change based on their life‐history traits. However, these traits are rarely considered when translocating mussels. To complicate matters, most mussel species have yet to be evaluated on how they respond to translocation, and for species where such information is available, adults are the primary focus. Addressing these knowledge gaps is critical for determining the appropriateness of translocation and improving its efficacy.